Menggali Kontribusi dari Diaspora: Studi tentang Diaspora India di UEA (Department of International Relations, Universitas Brawijaya, 2022)
India is currently one of the countries that is showing massive economic growth, even according to Goldman Sachs projections in 2050 India will be in the third position as the country with the largest economy in the world. Economic growth is certainly supported by various sectors, one of which is a large workforce base which is then channeled through migration activities which eventually form a diaspora known as Non-recident Indians (NRIs) and Person of Indian Origin (PIO) with a total number of 30,995 .729 inhabitants and spread in 210 countries in the world. The United Arab Emirates (UAE) is the main destination country of migration for NRIs and PIOs after the United States and Pakistan, based on existing data the number of NRIs and PIOs in the UAE in 2017 was 3,500,000. The Indian government then used NRIs and PIOs in the UAE to make a significant contribution to India's development as country of origin including remittances and foreign direct investment (FDI).Keywords: India and UAE, Indian Development, UEA Development, Remittances, Foreign Direct Investment (FDI).